+0  
 
0
253
1
avatar

12 - 2x + 5 = -2 + (x-3)

Guest Oct 29, 2017

Best Answer 

 #1
avatar+7324 
+1

12 - 2x + 5  =  -2 + (x - 3)

 

We don't need to keep the parenthesees since there is just addition outside them.

 

12 - 2x + 5  =  -2 + x - 3      Combine like terms on both sides.

 

17 - 2x  =  -5 + x             Add  5  to both sides of the equation.

 

5 + 17 - 2x  =  x              Add  2x  to both sides.

 

5 + 17  =  2x + x             Combine like terms again.

 

22  =  3x         Divide both sides by  3 .

 

\(\frac{22}{3}\)  =  x

hectictar  Oct 29, 2017
 #1
avatar+7324 
+1
Best Answer

12 - 2x + 5  =  -2 + (x - 3)

 

We don't need to keep the parenthesees since there is just addition outside them.

 

12 - 2x + 5  =  -2 + x - 3      Combine like terms on both sides.

 

17 - 2x  =  -5 + x             Add  5  to both sides of the equation.

 

5 + 17 - 2x  =  x              Add  2x  to both sides.

 

5 + 17  =  2x + x             Combine like terms again.

 

22  =  3x         Divide both sides by  3 .

 

\(\frac{22}{3}\)  =  x

hectictar  Oct 29, 2017

7 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.